Adiponectin receptor agonist AdipoRon attenuates calcification of osteoarthritis chondrocytes by promoting autophagy. Issue 5 (3rd January 2020) - Duan, Zhi‐xi; Tu, Chao; Liu, Qing; Li, Shuang‐qing; Li, Yi‐han; Xie, Peng; Li, Zhi‐hong
Abstract: Cartilage calcification contributes to the development and progression of osteoarthritis (OA). It has been well‐investigated adiponectin regulates vascular calcification. The purpose of this study is to investigate the therapeutic value and the molecular mechanism of AdipoRon, an adiponectin receptor agonist, on the chondrocytes calcification. Primary chondrocytes were isolated and cultured from normal cartilage and OA cartilage. The calcification in tissues was evaluated by inductively coupled plasma/atomic emission spectroscopy and alizarin red S staining. The calcification in chondrocytes was determined using the alkaline phosphatase (ALP) staining and an ALP assay kit. The cellular effects of AdipoRon were assessed by immunofluorescence staining and Western blot analysis. We found that calcification was significantly increased in OA cartilage tissues and cells. Importantly, the degree of calcification and ALP activity of the OA chondrocytes was decreased upon the treatment with AdipoRon. The AdipoRon‐induced cellular effects, including the reduction of the calcification of chondrocytes and improvement of autophagy, were blocked by dorsomorphin, an 5′‐adenosine monophosphate‐activated protein kinase (AMPK) inhibitor. Moreover, autophagy activation by AdipoRon was mediated by the AMPK‐mammalian target of rapamycin (mTOR) signaling pathway. Our results suggest that AdipoRon significantly alleviates the calcification of OA chondrocytes via activating AMPK‐mTOR signaling to promote autophagy. Therefore, AdipoRon could be a potential therapeutic agent for the prevention and treatment of OA. Abstract : In this study, we found that AdipoRon significantly alleviate the calcification of OA chondrocytes via activating AMPK‐mTOR signaling to promote autophagy. Therefore, AdipoRon could be a potential therapeutic agent for the prevention and treatment of OA.